1982
DOI: 10.1051/rnd:19820717
|View full text |Cite
|
Sign up to set email alerts
|

Influence de l'alimentation minérale de la truie sur le taux de masculinité à la naissance

Abstract: Summary. Effect on sex ratio of mineral diet in sows.This paper reports a study on sows to check the theory of Stolkowski which hypothesizes that mineral imbalance in the diet of the female before fertilization affects the sex ratio of the progeny. Relative excess of Na and K ions (NaK diet) would favour the birth of males, while relative excess of Ca 2+ and Mg 2+ ions (CaMg diet) would favour the birth of females. We carried out two successive experiments. In the first, sows were given the diet for about 34 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 4 publications
0
2
0
3
Order By: Relevance
“…For instance, Herbst for the first time showed that potassium concentration in seawater could change the sex ratio from 0.1 to 10 (30). Later studies showed that a high intake of K + and Na + and a low intake of Ca ++ and Mg ++ increased the sex ratio in sows and rats (31,32). Some studies tested these hypotheses before Mathew et al (23) and Noorlander et al (22) and reported similar findings, but as their electronic full texts were not available, the researchers of this study decided to exclude them from the review (33,34).…”
Section: Discussionmentioning
confidence: 97%
“…For instance, Herbst for the first time showed that potassium concentration in seawater could change the sex ratio from 0.1 to 10 (30). Later studies showed that a high intake of K + and Na + and a low intake of Ca ++ and Mg ++ increased the sex ratio in sows and rats (31,32). Some studies tested these hypotheses before Mathew et al (23) and Noorlander et al (22) and reported similar findings, but as their electronic full texts were not available, the researchers of this study decided to exclude them from the review (33,34).…”
Section: Discussionmentioning
confidence: 97%
“…D'autre part, contrairement aux batraciens, dans le cas de certains mammifères l'on connaissait les caryotypes et on savait que les expressions génotypique et phénotypique du sexe correspondaient (sauf cas pathologiques). La communauté des chercheurs travaillant sur la reproduction commence par exprimer son scepticisme (Thibault, 1975;Durlach et Pechery, 1977;Courot, 1981) et une équipe de chercheurs réplique l'expérience et obtient des résultats négatifs (Bolet et al, 1982). • Ne réagissant pas à ces objections, Stolkowski préfère prendre contact avec des médecins et des gynécologues pour étudier les modalités de l'application des premiers résultats au cas humain.…”
Section: "L'affaire"unclassified
“…On pourrait mobiliser de nombreux exemples justifiant ces sévères accusations: -Un travail sur le caryotype de cellules de rat en culture, qu'il avait commandé à un pédiatre préparant un doctorat de biologie, pour pallier l'impossibilité d'effectuer des caryotypes de batraciens, fera l'objet d'une publication et d'une thèse de troisième cycle (Sebaoun, 1966;Sebaoun et Stolkowski, 1967) et conclura néga tivement; cependant, seul le matériel d'étude sera incriminé. -Devant la vigueur des critiques, l'INRA (comme nous l'avons déjà signalé plus haut) a accepté d'arbitrer la controverse mais les résultats furent négatifs et publiés (Bolet et al, 1982). 14 Ceci n'a en rien arrêté Stolkowski et certains de ses colla borateurs.…”
Section: Hommesunclassified
See 1 more Smart Citation
“…Evidence subsequently was reported that supported this theory (Stolkowski and Choukroun, 1981). Studies by Bolet et al (1982), however, failed to show a consistent relationship between dietary mineral excesses and sex ratio in pigs. Although our study involved possible deficiencies rather than excesses of Na, the association of low Na intake and decreased proportion of male newborn pigs supports the hypothesis of Stolkowski (1967).…”
Section: Experiments 2 Sow Weights Sow Weightmentioning
confidence: 99%